2020
DOI: 10.1186/s12911-020-1033-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating usability of mobile health applications in Bangladesh

Abstract: Background: Lack of usability can be a major barrier for the rapid adoption of mobile services. Therefore, the purpose of this paper is to investigate the usability of Mobile Health applications in Bangladesh. Method: We followed a 3-stage approach in our research. First, we conducted a keyword-based application search in the popular app stores. We followed the affinity diagram approach and clustered the found applications into nine groups. Second, we randomly selected four apps from each group (36 apps in tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 38 publications
2
64
0
4
Order By: Relevance
“…Thus, numerous mHealth activities are already under process in developing countries especially Bangladesh. Overall, the findings suggest that the usability of the mHealth apps in Bangladesh is not satisfactory in general and could be a potential barrier for wider adoption of mHealth services (Islam et al, 2020). Many private and public sector have invested millions of dollar in this domain.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, numerous mHealth activities are already under process in developing countries especially Bangladesh. Overall, the findings suggest that the usability of the mHealth apps in Bangladesh is not satisfactory in general and could be a potential barrier for wider adoption of mHealth services (Islam et al, 2020). Many private and public sector have invested millions of dollar in this domain.…”
Section: Introductionmentioning
confidence: 90%
“…Though, a handful number of researches have been conducted on mHealth adoption and reported the key contributors, only a few numbers of studies have been explicitly focused on mHealth apps adoption in the context of Bangladesh (i.e. Islam et al, 2020;Rahman et al, 2018;Alam et al, 2020;Karim et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some apps provide virtual assistance through interacting with people in natural language and voice. 3) Current status -Most of the applications (i.e., 18 out of 25 applications) provide the current status and statistics from a local (specific-country context) and a global perspective through data-sheets and data visualizations. Such status includes the number of confirmed infected people, recovery, death, incubation period, etc.…”
Section: A App Objective and Featuresmentioning
confidence: 99%
“…Finally, only a few mobile applications have been developed for coronavirus so far. We note that prior research found that most mobile health applications developed in Bangladesh suffer from usability problems [76] [78] . Prior works suggest that usability is the key for wider adoption and continued use of services [79] .…”
Section: Discussionmentioning
confidence: 85%